2020
DOI: 10.3390/su12052137
|View full text |Cite
|
Sign up to set email alerts
|

Land Concentration, Land Grabbing and Sustainable Development of Agriculture in Romania

Abstract: Land grabbing has become a priority topic in academic research and a political concern, due to interests in the dynamics of the phenomenon and its negative impact on the sustainable development of agriculture in rural areas. This phenomenon generates changes in production systems of agriculture with adverse environmental consequences, adversely affects socio-economic and cultural conditions and leads to lower overall efficiency in agriculture. This article analyses the links between land concentration, land gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 21 publications
0
26
0
Order By: Relevance
“…Future research should concentrate on increasing production efficiency and land-use concentration by the introduction of advanced agricultural technology to ensure environmental conservation and avoid natural damages. Burja et al (2020) emphasized that land grabbing in Romania has had a significant dimension compared to other Member States of the EU leading to an inadequate agrarian structure and adverse effects on the sustainable performance of agricultural holdings and the sustainable development of rural areas.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Future research should concentrate on increasing production efficiency and land-use concentration by the introduction of advanced agricultural technology to ensure environmental conservation and avoid natural damages. Burja et al (2020) emphasized that land grabbing in Romania has had a significant dimension compared to other Member States of the EU leading to an inadequate agrarian structure and adverse effects on the sustainable performance of agricultural holdings and the sustainable development of rural areas.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Historical, economic, and biophysical factors mean that traditional subsistence and semi-subsistence agriculture is still more common in parts of Eastern Europe compared with the rest of the EU (Sutcliffe et al 2015, Hartel et al 2016, Burja et al 2020. Since joining the EU in 2007, Romania has been considered one of the EU's foremost biodiversity hotspots, particularly in terms of farmland-associated diversity (Loos et al 2014).…”
Section: High Nature Value In the European Union And Romaniamentioning
confidence: 99%
“…However, due to unclear definition criteria (Beaufoy et al 2012), reported values range between 15-39% (Page et al 2012, Gavrilescu 2017. Particularly in remote areas and economically marginal agricultural lands, farming in rural Romania has prevailed at subsistence and semi-subsistence levels (Burja et al 2020). Roughly 93% of Romania's farm holdings have less than 5 ha of agricultural land, and the diverging trend of land-use intensification is visible given that 70% of agricultural land lies in the hands of 7% of holdings (European Network of Rural Development 2015).…”
Section: High Nature Value In the European Union And Romaniamentioning
confidence: 99%
See 1 more Smart Citation
“…The fact that Romanian agriculture still remains underdeveloped (as compared to the other Member States) has encouraged a lot of foreign investments in recent years. As a result of this process, which sometimes takes the form of outright land grabbing (Burja et al 2020, Bouniol 2013, the market production of food in Romania has become increasingly dominated by very large companies operating on an international scale*. This is clearly visible within the livestock sector.…”
mentioning
confidence: 99%